Effectiveness of Child and Infant Airway Management Training for Midwifery Students in Jambi - Agus Pairi; Suryadi Imran (Westscience Press, 2024)
Choking often occurs in children and babies which causes airway obstruction, either partial airway obstruction or total airway obstruction. If help is not given immediately, it can result in death in children and babies. This research was conducted to determine the level of knowledge and skills of midwifery students in airway management in infants and children with airway obstruction due to choking. The research aims to determine students' knowledge and skills in airway management in infants and children with choking cases using a comparative research method, namely assessing knowledge before and after being given training, the sample used was 36 respondents, and the results showed an increase in students' knowledge after being given training with a value The pretest average for knowledge was 51.72% to 86.14%, while for skills there was an increase in knowledge after the test, with an average score of 93.31%. The conclusion is that this training can have an impact on increasing students' knowledge and skills so that when students practice and find cases of airway obstruction, they can do it as optimally as possible.